Nanostructures and Self-Assembly of Organogels via Benzimidazole/Benzothiazole Imide Derivatives with Different Alkyl Substituent Chains. (22nd April 2013) - Shen, Xihai; Jiao, Tifeng; Zhang, Qingrui; Guo, Haiying; Lv, Yaopeng; Zhou, Jingxin; Gao, Faming
Abstract : New benzimidazole/benzothiazole imide derivatives with different alkyl substituent chains were designed and synthesized. Their gelation behaviors in 22 solvents were tested as novel low-molecular-mass organic gelators. The test showed that the alkyl substituent chains and headgroups of benzimidazole/benzothiazole residues in gelators played a crucial role in the gelation behavior of all compounds in various organic solvents. More alkyl chains in molecular skeletons in present gelators are favorable for the gelation of organic solvents. SEM and AFM observations revealed that the gelator molecules self-assemble into different aggregates from wrinkle, lamella and belt to dot with change of solvents. Spectral studies indicated that there existed different H-bond formation between imide groups and hydrophobic force of alkyl substituent chains in molecular skeletons. The present work may give some insights into design and character of new organogelators and soft materials with special molecular structures.